The Ontario Birth Study: A prospective pregnancy cohort study integrating perinatal research into clinical care. Issue 3 (11th May 2018) - Anderson, Laura N.; Knight, Julia A.; Hung, Rayjean J.; Hewko, Sheryl L.; Seeto, Ryan A.; Martin, Mary‐Jean; Fleming, Alison; Maguire, Jonathon L.; Matthews, Stephen G.; Murphy, Kellie E.; Okun, Nan; Jenkins, Jennifer M.; et al.
Abstract: Background: Pregnancy and early childhood represent critical periods that impact health throughout the life‐course. The Ontario Birth Study (OBS) is a pregnancy cohort study designed as a platform for research on pregnancy complications, maternal and infant health, and the developmental origins of health and disease. Methods: Pregnant women <17 weeks gestational age were recruited between 2013 and 2015 from antenatal clinics at Mount Sinai Hospital, Toronto, Canada. Life style and diet questionnaires, biospecimens, and clinical data were collected throughout the pregnancy and postpartum period at the time of clinical care. The OBS was integrated into clinical care to reduce participant burden, improve efficiency, and increase research potential. Results: There were 3181 eligible women approached for recruitment and 1374 (43%) participated in the study. Among the 1374 participants, 1272 (93%) delivered a liveborn infant and were followed to 6‐10 weeks postpartum. Of the 1272 women who completed the study, 98% had at least one pregnancy blood sample collected, 97% had vaginal swabs collected, 90% completed the prenatal life style questionnaires, and 78% completed the Diet History Questionnaire. Most women (88%) were ≥30 years of age, 55% had no previous children, 24% were overweight or obese pre‐pregnancy and 78% of parents had postsecondary education. Most pregnancies were singleton (3% twins), 34% delivered by caesarean section, and 6% preterm (<37 weeks gestation). Conclusions: The OBS is a contemporary cohort with detailed data including banked biospecimens for studies of pregnancy health and the gene‐environment interactions that establish developmental trajectories to health, learning, and social functioning.